ADVERTISEMENT EFFECTIVITY ANALYSIS ON FOODGRAM TOWARDS FOOD SELLING VOLUME (SURVEY ON ACCOUNT PROMOTION SERVICE USERS @DUNIAKULINERBDG) - Sri Wahyuni; Agus Sudono; Armandha Red (Jurnal Industri Parawisata, 2023)
The aim of this research is to analyze the dominant factors that affect advertising efficiency and to set up strategies to optimize those factors in order to increase sales volume. The research method used is the quantitative method with correlation studies and SWOT analysis. Researcher disseminate cohesion using simple random sampling techniques to 100 users of the foodgram @duniakulinerbdg account promotion service. The result shows that advertising efficiency on foodgram simultaneously affects sales volume with a ratio of 0.752, which means that it has a strong correlation level. Furthermore, the result of t-test partial proved that empathy and communication as sub variable of independent variabel partially effect sales volume. Thus, those two aspects need to be optimized when promoting their product through foodgram.